Religious lay in clerical institutes. Mixed institutes, real posibility or dead end? - Bahillo Ruiz, Teodoro (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2016)
Lay consecration has own value regardless of the sacred Ministry. The presence of lay members with clerics within a clerical Institute raises legal issues clarify about to participation in the Government and the mission. Discussed the opportunity to be recognized as clerical institutes and raises the regulation possibility of recognition as mixed institutes to better safeguard the dignity and identity of its members. A mixed Institute would be one in which the original design all the members-priest ant those who were not priests— were considered equal each other with equal rights and obligations. Neither regulation nor the practice of the Holy See has changed the provisions of the can. 588: institutes are lay or clerical. The request for a full participation in the Government of institutes by the brothers only finds response in particular cases when the Supreme authority approve the constitutions: local superiors, vicar provincial, members of Councils at all levels. The complex of faculties granted by the canonical law to the major superiors of the clerical institutes demands that the Government of these institutes has been booked to clerics.
Keywords: Lay Institute; Religious Brothers; Major Superior; Power of governance; Indifferent Institutes.